Study on Microstructure and Property of Hot-dip 55% Al-Zn Alloy Coating on 35CrMo Sucker Rod Surface. Issue 4 (May 2019) - Jing, Wu; Dong, Liu; Linlin, Zhang; Xiaopeng, Yang; Xu, Chi
Abstract: The formation process and corrosion resistance of 55%Al-Zn alloy coating for 35CrMo sucker rod are studied in this paper. The study shows that reduction of Si content in coating bath can reduce Fe dissolving and also keep size of sucker rod stable at the same time. The coating is divided into intermediate layer and Al-Zn coating from inside to the outside. The main components of the intermediate compound layer are made up of Fe2 Al5, FeAl3 and Al0.5 Fe3 Si0.5 by XRD analysis. Corrosion results indicate that the ratio of the weight loss between coated and uncoated sucker rod is 5.9:1 and the corrosion current density is 3:1.